2013
DOI: 10.16925/sp.v9i18.543
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la suplementación de capsaicina como estimulante inmunológico en pollos Ross

Abstract: La capsaicina es una sustancia activa que está presente en el ají picante. En las aves, los capsaicinoides han sido investigados con el fin de prevenir problemas asociados a Salmonella. La tendencia mundial a disminuir los antibióticos como promotores de crecimiento (apc) ha incrementado las investigaciones que busquen reemplazarlos por alternativas naturales como el uso de capsaicinoides. El objetivo de este trabajo fue evaluar el efecto de la adición de capsaicinoides en concentración de 10, 30 y 50 ppm sumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Regarding the effect of food additives in the diet, it has been observed that in poultry, capsaicin can act as a growth promoter, since a tendency since to increase antibodies has been seen as the capsaicin dose is increased in the diet (Sanabria et al, 2013). Also, as a regulator of normal temperature in chickens with fever induced by LPS (Mahmoud et al, 2007) decreases the heterophil:lymphocyte ratio (Prieto and Campo, 2010), improved jejunal development (width and surface area of the villi) and increased enzymatic activity (lipase and trypsin) (Li et al, 2022).…”
Section: Capsaicin Effectmentioning
confidence: 99%
“…Regarding the effect of food additives in the diet, it has been observed that in poultry, capsaicin can act as a growth promoter, since a tendency since to increase antibodies has been seen as the capsaicin dose is increased in the diet (Sanabria et al, 2013). Also, as a regulator of normal temperature in chickens with fever induced by LPS (Mahmoud et al, 2007) decreases the heterophil:lymphocyte ratio (Prieto and Campo, 2010), improved jejunal development (width and surface area of the villi) and increased enzymatic activity (lipase and trypsin) (Li et al, 2022).…”
Section: Capsaicin Effectmentioning
confidence: 99%